The Relationship of Age, Educational Background, and Physical Activity on Female Students with Anemia - Lukman Dwi Priyanto (Universitas Airlangga, 2018)
Background: Anemia has been claimed as the second most contributing cause of disability, which is one of the global health problems. The national prevalence of anemia in female was relatively high (23,90%) compared to male (18,40%). Purpose: This study was aimed to analyze the relationship between age, educational background, and physical activity on anemia incident of a female student in the Islamic Boarding School in Surabaya. Methods: This study was analytic observational with a cross-sectional design. There were 45 female students in the study population, while 31 of them were selected as respondents through simple random sampling. Data were obtained primarily from questionnaire and the stripe test by medical worker and analyzed with the chi-square test. Results showed the prevalence of anemia was 83,90%. The proportion of anemia in Islamic Junior Highschool students was 90,90%. Meanwhile, the proportion of moderate physical activity with anemia was 94,40%. Results: Based on chi-square test, the age factor has p = 0,26, educational background p = 0,62, and physical activity p = 3,55. Conclusion: There was no significant correlation between age, educational background, and physical activity with anemia in female students of Islamic Boarding School in Surabaya.